C239S Mutation in the β-Tubulin of Phytophthora sojae Confers Resistance to Zoxamide - Cai, Meng; Miao, Jianqiang; Song, Xi; Lin, Dong; Bi, Yang; Chen, Lei; Liu, Xili; Tyler, Brett M. (Frontiers in Microbiology, 2016)
Zoxamide is the sole β-tubulin inhibitor registered for the control of oomycete pathogens. The current study investigated the activity of zoxamide against Phytophthora sojae and a baseline sensitivity was established with a mean EC50 of 0.048 μg/ml. Three stable resistant mutants with a high resistance level were obtained by selection on zoxamide amended media. Although the development of resistance occurred at a low frequency, there were no apparent fitness penalty in the acquired mutants in terms of growth rate, sporulation, germination and pathogenicity. Based on the biological profiles and mutagenesis rate, the resistance risk of P. sojae to zoxamide can be estimated as low to medium. Further investigation revealed all the zoxamide-resistant mutants had a point mutation of C239S in their β-tubulin. Zoxamide also exhibited high activity against most species from the genus Pythium in which only Py. aphanidermatum was found resistant to zoxamide and harboring the natural point mutation S239 in the beta-tubulin. Back-transformation in P. sojae with the mutated allele (S239) confirmed the C239S mutation induced resistance to zoxamide, and the resistance level was positively related to the expression level of the mutated gene. In contrast, the overexpression of the wild type gene was unable to cause zoxamide resistance. It is the first report on the resistance molecular mechanism of zoxamide in oomycetes. Based on our study, C239 is supposed to be a key target site of zoxamide, which distinguishes zoxamide from benzimidazoles and accounts for its low resistance risk. The result can provide advice on the design of new β-tubulin inhibitors in future.